The Oxford handbook of the Ethiopian economy - Fantu Cheru, 1949-; Cramer, Christopher, Dr.; Oqubay, Arkebe (Oxford : Oxford University Press, 2019)
From a war-torn and famine-plagued country at the beginning of the 1990s, Ethiopia is today emerging as one of the fastest-growing economies in Africa. This Oxford Handbook focuses on structural transformation to understand Ethiopia's unique model of development.
Ethiopia's Transition from a Traditional to a Developing Economy (1890s-1960s) / Bekele Shiferaw -- Infrastructure and Economic Transformation in Ethiopia / Seid Nuru -- Financial Balances and the Development of the Ethiopian Economy / Ken Coutts, Christina Laskaridis -- Trade Policy in Ethiopia (1991-2016) / Berihu A. Gebrehiwot -- Livelihoods and Mobility in the Border Regions of Ethiopia / Laura Hammond PhD -- Green and Climate Resilient Transformation in Ethiopia / Haileselassie Medhin, Alemu Mekonnen PhD -- Assessing Poverty Trends in Ethiopia (1990-2015) / John Sender -- Poverty and inequality in Ethiopia (1996/96-2015/16) / Mesele Araya, Tassew Woldehana PhD -- Growth, Poverty, and Distribution in Ethiopia / Abebe Shimeles -- Ethiopia's Changing Demography / Assefa Hailemariam PhD -- Land Tenure and Land Policy in Ethiopia (1950-2000) / Teferi Abate Adem -- Economic Policy and Food Security in Ethiopia / Deborah Johnston PhD, Helen Walls -- Changes in Child Undernutrition in Ethiopia (2000-2016) / Jenna Golan, Derek Headey PhD, Kalle Hirvonen, John Hoddinott -- Social Protection in Ethiopia / John Hoddinott, Alemayehu Seyoum Taffesse PhD -- Education and Economic Development in Ethiopia (1991-2017) / Zinabu Samaro Rekiso -- The Transformation of Smallholder Crop Production in Ethiopia (1994-2016) / Alemayehu Seyoum Taffesse PhD -- Rural Finance and Smallholder Farming in Ethiopia / Kibrom Abay, Guush Berhane PhD -- Performance and Institutions of the Ethiopian Coffee Sector / t Building an industrial workforce in Ethiopia / Carlos Oya PhD -- The Private Sector in Ethiopia's Transformation / Mulu Gebreyesus PhD -- Light Manufacturing in Ethiopia: The Apparel Export Industry / Cornelia Staritz, PhD, Lindsay Whitfield, PhD -- Technological Learning and Industrialization in Ethiopia / Taferre Tesfachew PhD -- The Legal Framework for the Protection of Foreign Direct Investment in Ethiopia / Won L. Kidane -- Rural-Urban Linkages in Ethiopia / t A 'New Structural Economics' perspective of SEZs in Ethiopia / Sarah Hager, Justin Lin, Jiajun Xu -- The Concept of a "Developmental State" in Ethiopia / t Ethiopia's 'Economic Diplomacy' and Regional Integration / Fantu Cheru, Zinabu Samaro Rekiso -- Constraints on the Ethiopian Floriculture Industry / Ayelech T. Mesele -- Institution Building for Industrialization: The Ethiopian Investment Commission / John Sutton -- The Interface between Federalism and Development in Ethiopia / Assefa Fiseha, Fiseha H. Gebresilassie -- Women's Empowerment in Rural Ethiopia / Annet A. Mulema, Likimyelesh Nigussie -- Ethiopia's Political Economy from the Imperial Period to the Present / Christopher Clapham -- Financing Ethiopia's Development / Mekonnen Manyazewal -- Economic Policy and Structural Transformation in Ethiopia / Mekonnen Manyazewal, Admasu Shiferaw PhD -- Ethiopian Financial Sector / Yohannes Ayalew Birru.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 5, 2019).
Keywords: Ethiopia -- Economic conditions -- 21st century; Ethiopia -- Economic conditions -- 1974-; Economic development -- Ethiopia; Ethiopia -- Economic policy